2013
DOI: 10.1016/j.worlddev.2012.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Declining Inequality in Latin America in the 2000s: The Cases of Argentina, Brazil, and Mexico

Abstract: Between 2000 and 2010, the Gini coefficient declined in 13 of 17 Latin American countries. The decline was statistically significant and robust to changes in the time interval, inequality measures and data sources. In depth country studies for Argentina, Brazil and Mexico suggest two main phenomena underlie this trend: a fall in the premium to skilled labor and more progressive government transfers. The fall in the premium to skills resulted from a combination of supply, demand, and institutional factors. Thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
168
1
23

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 359 publications
(204 citation statements)
references
References 17 publications
12
168
1
23
Order By: Relevance
“…They argue that income inequality increased in the 1990s mainly because of higher wage inequality due to the importance of labour income for total household income. Lustig et al (2013) argue that the secular deregulation of labour markets, combined with the liberalization of investment and imports and a fixed exchange rate (hard peg to the US Dollar), which undermined the competitiveness of Argentina's exports, were all factors that contributed to the higher levels of inequality observed during the period.…”
Section: Recent Research On Income Inequality In Argentinamentioning
confidence: 99%
See 1 more Smart Citation
“…They argue that income inequality increased in the 1990s mainly because of higher wage inequality due to the importance of labour income for total household income. Lustig et al (2013) argue that the secular deregulation of labour markets, combined with the liberalization of investment and imports and a fixed exchange rate (hard peg to the US Dollar), which undermined the competitiveness of Argentina's exports, were all factors that contributed to the higher levels of inequality observed during the period.…”
Section: Recent Research On Income Inequality In Argentinamentioning
confidence: 99%
“…According to an array of research (Cornia, 2014;Lustig et al, 2013;Maurizio, 2014), the implementation of pro-labour policies in Argentina, starting in 2002/2003, marked the turning point in the evolution of inequality. Policies included favouring union vindications, collective bargaining and an increase in the minimum wage.…”
Section: Recent Research On Income Inequality In Argentinamentioning
confidence: 99%
“…Sin embargo, las fuerzas del mercado, mediante los cambios en la composición de la oferta y demanda de trabajo por cualificación, también son factores explicativos de los cambios en los salarios agregados de los estados mexicanos en el periodo de estudio. Por un lado, existen trabajos que evidencian que los cambios en la composición de la oferta relativa de trabajadores cualificados y el bajo ritmo al que se ha incrementado su demanda parecen dominar, debidos probablemente al incremento sustancial del gasto de gobierno dirigido a expandir la educación básica (Montes, 2006;Campos et al, 2012;Esquivel et al, 2012y Lustig et al, 2013. Por otro lado, Gasparini et al (2011) y Manacorda et al (2010 encuentran que los cambios en la composición de la demanda relativa a través del incremento de trabajo cualificado son los dominantes, los cuales fueron sólo parcialmente compensados por un incremento en su oferta relativa.…”
Section: Conclusionesunclassified
“…During the last decade, Latin America has experienced an important decrease in household income inequality (Lustig et al 2013;Alvaredo and Gasparini 2015). Recent studies have shown that the main driver must have been the reduction in wage inequality (Abad and Lindert 2017;De la Torre et al 2017).…”
Section: Introductionmentioning
confidence: 99%